The Sovereign Default Problem in the Eurozone - Why Limited Liability Resulted in Excessive Debt Accumulation and How Insurance Can Counteract - Nadjeschda Katharina Arnold (ifo Institut - Leibniz-Institut für Wirtschaftsforschung an der Universität München, 2016)
This thesis was written by Nadjeschda Katharina Arnold while having been a research assistant at the Center for Economic Studies (CES) at the University of Munich. It was completed in December 2014 and accepted as a doctoral thesis by the Department of Economics at the University of Munich in May 2015. The thesis analyses the sovereign default problem in the Eurozone in two parts. Part I explains why limited liability may have resulted in excessive debt accumulation: A commitment problem of the European Monetary Union to no bailouts may have banished interest rate risk premiums inducing its member states to ignore a part of their original repayment obligation in their debt decision. Part II shows how insurance can restore optimal incentives of debt accumulation by replacing the interest rate risk premiums with insurance premiums.
Keywords: G11; G12; G22; H63; H77; 330; European debt crisis; sovereign debt; bailout; monetary union; debt management; Staatsbankrott; Schuldenkrise; Schuldenübernahme; Beschränkte Haftung; Versicherungsschutz; Eurobond; Europäischer Stabilitätsmechanismus; Eurozone; EU-Staaten